José! : born to dance : the story of José Limón - Reich, Susanna (Simon & Schuster Books for Young Readers, 2005)
In 1908 a baby boy was born in Culiacan, Mexico, kicking like a roped steer. BAM! BAM! BAM! His name was Jose Limon. Though he and his family fled civil war in their homeland by escaping to the United States when Jose was just seven years old, he would never forget the sounds and movements of his birthplace. Then Jose followed his heart to New York City. He fell in love with the shimmering city that towered above him: marble, stone, brick, and steel. He wanted to give a gift to the world and discovered the world of dance. There was no stopping Jose Limon, who went on to become one of the greatest modern dancers who ever lived. Award-winning author Susanna Reich and acclaimed illustrator Raul Colon tell the story of this great Mexican dancer in a picture book biography as beautiful and graceful as Jose's dance itself.